Assessing the Nasalance of Native Mandarin Speakers in Mandarin and English - Pua, Eshan (East Carolina University, 2017)
Objective: To determine whether native Mandarin speakers show a difference in nasalance measurement in their native language compared to English and analyze the effect of predictors on nasalance scores. Design: Participants completed a questionnaire about cultural and linguistic background. All participants recorded three Mandarin sentences and vowels, and three English sentences and vowels, designed to phonetically match Mandarin speech stimuli. Nasalance measurements were taken from the Nasometer II 6450. Participants were randomly selected to repeat recordings for test-retest reliability. Participants and setting: The participants included 45 native Mandarin-speakers (20 males, 25 females) from mainland China between 20 and 54 years of age. All participants were tested in the speech laboratory of East Carolina University. Results: A paired samples t-test revealed a significant difference between mean nasalance scores of English and Mandarin sentences (p < 0.008). Scores for English and Mandarin vowels did not yield significant results. A multiple linear regression model revealed significant gender-based differences (p < 0.05). Age, English language exposure, mean English language preference and dialect did not yield significant results. Conclusions: Native Mandarin speakers yield different nasalance scores in their native language compared to English. This confirms that separate nasalance score norms are needed for the Mandarin language. Gender-based differences should be considered in the collection and analysis of nasalance scores. Reported Nasometer scores can be used for preliminary normative data.
Keywords: Mandarin; Chinese; English; nasalance; nasometer; resonance; Speech Acoustics; Language